PENANAMAN NILAI AGAMA PADA ANAK USIA DINI DI RAUDHATUL ATHFAL DARUL ULUM MUARAMAIS JAMBUR MANDAILING NATAL - Suryadi Nasution; Resdilla Pratiwi (AWLADY : Jurnal Pendidikan Anak, 2022)
The objective of this research is to describe the form of religious orientation that was applied in Raudhatul Athfal Darul Ulum Muara Mais district of Mandailing Natal. This study uses qualitative research that emphasizes direct observation by contextual analysis in observing each issue. The method of maintaining values is to formulate each activity in Islamic Discourse. Starting with the recognition of the concept, and practicing of the worship, exemplary, tourism and inculcate ideals.